2016
DOI: 10.3347/kjp.2016.54.4.407
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Imported Malaria and Species of Plasmodium Involved in Shandong Province, China (2012-2014)

Abstract: Malaria remains a serious public health problem in Shandong Province, China; therefore, it is important to explore the characteristics of the current malaria prevalence situation in the province. In this study, data of malaria cases reported in Shandong during 2012-2014 were analyzed, and Plasmodium species were confirmed by smear microscopy and nested-PCR. A total of 374 malaria cases were reported, 80.8% of which were reported from 6 prefectures. Of all cases, P. falciparum was dominant (81.3%), followed by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 29 publications
0
14
0
Order By: Relevance
“…Nevertheless, there was an increasing trend of the malaria cases presented in Shandong from 2012 to 2015 due to the proportion of imported malaria (100%, 586/586) and the majority of them were P . falciparum cases returning from African countries (79.9%, 468/586) 29 , 30 . Since 2009, DHA + PQ and AS + AQ have been applied to against uncomplicated P .…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, there was an increasing trend of the malaria cases presented in Shandong from 2012 to 2015 due to the proportion of imported malaria (100%, 586/586) and the majority of them were P . falciparum cases returning from African countries (79.9%, 468/586) 29 , 30 . Since 2009, DHA + PQ and AS + AQ have been applied to against uncomplicated P .…”
Section: Discussionmentioning
confidence: 99%
“…Once errors happened during this program, the false negative would probably present. For example, in a previous study, there were 10 malaria cases failed to be identified by molecular methods due to the problems in nucleic acid extraction until reasons were found out by repeated experiments [54]. Therefore, the combining use of the four methods is quite necessary and highly recommended.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, prevention and treatment against P. falciparum should be highly considered in Wuhan. By the year elapsed, the Plasmodium species leading to imported malaria were becoming diversity just as the situation in another region of China, Shandong province [54]. The increase of imported P. vivax and P. ovalis cases may cause the re-introduction of malaria in those regions without cases [57,58].…”
Section: Discussionmentioning
confidence: 99%
“…Surveillance is highly recommended as a key intervention in the post-malaria elimination stage. However, decisive and rapid response to imported malaria is vital to prevent re-introduction and sustain malaria elimination [11,27,29,[49][50][51][52][53]. A shift from community to hospitals at the county and higher level for primary diagnosis was also recorded [8,27], indicative of a more active role of the main city airports as ports of entry.…”
Section: Gaps and Challengesmentioning
confidence: 99%